2013
DOI: 10.1146/annurev-bioeng-071812-152428
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Vascularization in Tissue Engineering

Abstract: Vascularization is one of the great challenges that tissue engineering faces in order to achieve sizeable tissue and organ substitutes that contain living cells. There are instances, such as skin replacement, in which a tissue-engineered substitute does not absolutely need a preexisting vascularization. However, tissue or organ substitutes in which any dimension, such as thickness, exceeds 400 μm need to be vascularized to ensure cellular survival. Consistent with the wide spectrum of approaches to tissue engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
216
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(226 citation statements)
references
References 142 publications
0
216
0
Order By: Relevance
“…Our finding that 90 % of all microvessels inside freshly seeded scaffolds stained positive for GFP indicates that this improved vascularisation was mainly caused by the reassembly of microvascular fragments into functional microvascular networks over time. This also resulted in higher tissue content inside the implants, further emphasising the importance of a sufficient vascularisation for the survival and successful incorporation of tissue constructs (Laschke et al, 2006;Auger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that 90 % of all microvessels inside freshly seeded scaffolds stained positive for GFP indicates that this improved vascularisation was mainly caused by the reassembly of microvascular fragments into functional microvascular networks over time. This also resulted in higher tissue content inside the implants, further emphasising the importance of a sufficient vascularisation for the survival and successful incorporation of tissue constructs (Laschke et al, 2006;Auger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The success of tissue engineering approaches depends on the establishment of an adequate vascularisation, which provides the basis for the onset of regenerative processes and guarantees the survival of cell-seeded implants (Laschke et al, 2006;Auger et al, 2013). Accordingly, various vascularisation strategies have been tested during the last years, ranging from the stimulation of angiogenesis at the defect site by sophisticated growth factor delivery systems to the generation of preformed microvascular networks inside tissue constructs prior to their implantation (Phelps and García, 2010;Novosel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We first referred to two classic endothelial angiogenesis-related pathways both in vitro and in vivo: VEGF signaling [6,7,22] and angiopoietin/TIE2 signaling [34,35]. However, the RNA-seq results did not show significant elevation of upstream ligands or receptors for these pathways in co-HUVECs within 24 h. Alternatively, unbiased analysis demonstrated that a large proportion of experimentally validated NF-kB target genes (mainly based on www.bu.edu/NF-kB/gene-resources/target genes) were upregulated upon coculture for 12 and 24 h in both co-HUVECs and co-HMSCs (Fig.…”
Section: Rna-seq Revealed Differential Gene Expression Profiles and Amentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), the stromal progenitor cells found in the bone marrow [3], were recently proved effective in vascular enhancement and protection [4,5]. Since tissue engineering is currently limited by the inability to adequately vascularize tissues surrounding the engineered constructs [6,7], the coimplantation of MSCs with human endothelial cells (ECs) recently succeed in creation of fully functional blood vessels under different circumstances in vivo [8][9][10], which could serve as a good solution for controlled vascularization. However, the cellular and molecular bases of MSCs-ECs interaction and their joint influence on endothelial vascularization were not fully understood.…”
mentioning
confidence: 99%
“…As previously mentioned, the incorporation of a mature, inter-connected vascular network within a tissue construct is vital in tissue engineering as it helps to prevent the development of a necrotic core due to nutrient deficiency of cells deep within the construct, and provides a readily perfusable network for nutrient perfusion throughout the construct during the fabrication stage, or after implantation in a patient [15] . The implantation of a pre-vascularized tissue construct minimizes the need for vasculogenic and angiogenic processes to occur after implantation, and has been shown to induce rapid vascularization and inosculation with host vasculature upon implantation into mice when compared to un-vascularized constructs [16] .…”
Section: Tissue Engineering For Regenerative Medicinementioning
confidence: 99%